(3ZQQ GdaQGFO hOQQ GdbdGFOs - (3CHh GdbGSe Ydj Hf GdMSjf Hf ehSi GdTQja GdeQJVj, GdTQja GdeQJVj,J (B436 (3g` s
(3ChdgG (B:s
(3JChjd bhdg JYGdi(B: (3Ndb GdEfSGf ef YLd(B" s
(3BNQgG (B:s
(3Edi BNQ eG Cedi s
(3GdfSNI GdNGeSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B295 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B81s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B1504 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1201s
(3eUOQ GbJfGA GdCUd (B:s
(3Hfi LGeY (B(987) s
Keywords: (3GdCOHs